Prior administration of oral rehydration solution promotes gastric emptying of enteral formula - TANIGUCHI, Hideki; TSUJI, Tomohiro; NAKADA, Etsuko (Jomyaku Keicho Eiyo, 2012)
Purpose: We investigated the effect of prior administration of clear fluids (oral rehydration solution and mineral water) on gastric emptying of enteral formula in healthy subjects as compared with non-consumption of clear fluids. Clear fluids were administered before feeding enteral formula. Methods: Seven healthy volunteers (2 males and 5 females) consumed oral rehydration solution (ORS group), mineral water (MW group), and no fluid (N group) in a crossover method before intake of enteral formula. The gastric emptying time of each enteral formula was determined by a standard gastric emptying test method using 13C excretion ratio in expired air, and changes (⊿ Tmax) in a maximum drug concentration time (Tmax) were evaluated as the primary endpoint. Results: ⊿ Tmax value of each group was compared with the Tmax of the N group. The gastric empting time was more promoted in the ORS group than in the MW group (⊿ Tmax(MW) vs. ⊿ Tmax(ORS): -5±15.0 min vs. -17.1 ±9.1 min; P=0.03). Conclusion: The results suggest that administration of oral rehydration solution before feeding enteral formula may promote gastric emptying of the enteral formula.